2023
DOI: 10.1002/epd2.20132
|View full text |Cite
|
Sign up to set email alerts
|

GABRB1‐related early onset developmental and epileptic encephalopathy: Clinical trajectory and novel de novo mutation

Abstract: Developmental and epileptic encephalopathy 45 (DEE45) is a neurogenetic disorder caused by heterozygous pathogenic variants of GABRB1, encoding the beta1 subunit of the GABA type A receptor. Only three infants with DEE45 have been reported so far, and a detailed description of the disease history of these patients is still lacking. We describe the clinical and genetic findings of a 21‐year‐old woman with DEE45 carrying a novel de novo GABRB1 mutation (c.841A>G, p.T281A). The patient presented at birth with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Monfrini et al (2023) described the clinical and genetic findings of a 21-year-old woman with DEE45 carrying a novel de novo GABRB1 variation (c.841A>G, p.T281A) which was the fourth report of a DEE45 patient (18). This patient presented at birth with hypotonia and focal apneic seizures evolving in a phenotype of epilepsy of infancy with migrating focal seizures that were refractory to anti-seizure medications.…”
Section: Discussionmentioning
confidence: 99%
“…Monfrini et al (2023) described the clinical and genetic findings of a 21-year-old woman with DEE45 carrying a novel de novo GABRB1 variation (c.841A>G, p.T281A) which was the fourth report of a DEE45 patient (18). This patient presented at birth with hypotonia and focal apneic seizures evolving in a phenotype of epilepsy of infancy with migrating focal seizures that were refractory to anti-seizure medications.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to IESS development, previous studies have shown alterations in neurosteroid sensitivity and decreased expression of GABA A receptors in IESS models and from a management perspective, one effective treatment of spasms is the GABA transaminase inhibitor, vigabatrin [ 36 , 46 , 47 ]. Interestingly, pathogenic variants in a number of GABA-related epilepsy genes have been implicated in the development of IESS, such as pathogenic variants in GABRB1 , GABRA1 and GABRB3 , highlighting the importance of GABA-related transmission in the development of IESS [ 48 , 49 , 50 , 51 ].…”
Section: Mechanisms Of Iessmentioning
confidence: 99%
“…Examples of other genes associated with IESS, which are mechanistically involved in GABAergic transmission, include GABRB1 , GABRB3 and GABRA1 , amongst others [ 48 , 49 , 50 , 51 ]. Specifically, the aforementioned genes encode subunits of GABA receptors.…”
Section: Spectrum Of Genetic Aetiologies Of Iessmentioning
confidence: 99%